Structural bioinformatics (Wiley, 2003)
The emerging discipline of structural bioinformatics comprises the development of computational technologies for methods of storage, retrieval, and analysis of the three-dimensional structure of biological macromolecules. Edited by Philip Bourne and Helge Weissig, this groundbreaking text provides a thorough understanding of the theories, associated algorithms, resources, and tools used in structural bioinformatics." "Readers will gain the ability to make effective use of protein, DNA, RNA, carbohydrate, and complex structures to better understand biological function. Molecular biologists, biochemists, biophysicists, and bioinformaticians in basic and clinical research, as well as undergraduate and graduate students in biology, medicine, and computer science, will find Structural Bioinformatics to be an essential addition to their professional and academic libraries.